Fluidised bed oxy-fuel gasification of coal: Interactions between volatiles and char at varying pressures and fuel feed rates. (November 2020) - Long, Xiangyi; Spiegl, Nicolas; Berrueco, Cesar; Paterson, Nigel; Millan, Marcos
Highlights: C conversion decreased with increasing pressure in a fluidised bed reactor. Char structure changed at the higher pressures. C conversion decrease was due to the formation and deposition of less reactive C. C deposit was caused by combination of intra and inter particle cracking of volatiles. Abstract: Fluidised bed gasification is a versatile technology in terms of load flexibility and ability to process various fuels. However, fluidised bed gasification processes are usually air-blown, making integration with CO2 capture difficult and expensive. Operation of a fluidised bed gasifier with O2 /recycled CO2 mixtures has been proposed as a route to overcome this drawback. In this work, the effect of pressure and fuel feed rate on the extent of gasification of German lignite in a CO2 rich atmosphere has been examined in a fluidised bed reactor (FBR). A 19% decrease in carbon conversion with increasing pressure from 5 to 20 bara was observed. The higher fuel feeding rates needed to maintain the gasification agent to coal ratio in the FBR at high pressures produces a larger concentration of tars in the reactor, which seems to cause deposition, by intra and inter particle reaction, on the char and reduces its reactivity.